Estudo da Eficiência de Eletrodos com e sem Filmes Depositados por Nitretação Aplicados ao Tratamento de Efluentes Têxteis Utilizando a Tecnologia de Eletrocoagulação - Oliveira, Juliene Tomé (2019)
The objective of the present work is to investigate the electrocoagulation technology (EC) in the removal of the Remazol Azul Brilhante R dye using aluminum and AISI 304 stainless steel electrodes modified by conventional plasma nitriding and with the cathodic cage configuration of stainless steel and titanium. The structural and morphological characterization of the electrodes was performed using X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), X-ray Energy Dispersion Spectroscopy (EDS) and Raman Spectroscopy. From the XRD analysis it was possible to observe the presence of AlN, Fe3N and Ti2N characteristic peaks in the treated samples. The AlGCT and AIGCT samples were the only ones that presented homogeneous thin films from the SEM results. Through the EDS, it was possible to identify the presence of the elements Al, Fe, Ti and N, constituents of the nitrites. The Raman spectra presented signals belonging to the vibrational modes (TA) and (TO) of the TiN and (E21) and (E1) of the AlN. After characterization of the electrode material, we carried out the electrocoagulation / oxidation experiments in order to investigate the efficiency in the removal of the dye using different electrodes. From these experiments it was possible to observe that the best percentages of color removal and TOC (99, 00% and 87,65%, respectively) were obtained when the stainless steel electrode treated with plasma with cathodic titanium cage was used in the process. In the study of electrocoagulation kinetics the results showed that the reaction follows a first order kinetics. The experiments using these electrodes presented lower energy consumption (2.99 kWh m-3) when compared to unmodified stainless steel electrodes. Thus, this study demonstrated that the use of electrodes modified by plasma deposition improves the treatment efficiency of the textile dye studied. In the experiments of EC using the EIGT electrode in the treatment of a textile effluent, the values of color removal, turbidity and TOC reached 93,72%, 94,14% and 40,08%, respectively.